Pendampingan Commercial Photography dan Caption Editing pada UMKM di Desa Ngargogondo - Achsa, Andhatu; Hutajulu, Dinar Melani; Putri, Nida Aprilia (Kreativasi : Journal of Community Empowerment, 2024)
The digital capabilities of MSMEs entrepreneurs in Ngargogondo Village are still limited, especially in the context of marketing. The purpose of the research is to provide knowledge of commercial photography and caption editing that is useful for improving business marketing in village MSMEs. The method of implementing the activity includes lectures, tutorials, and discussions. The results of the activity showed that participants gained increased skills in digital marketing, were able to make good commercial photos, and were able to determine the right caption for the product to be marketed. This activity is not only useful in increasing knowledge but also the technical skills of participants in digital marketing.